Are We There Yet, Daddy? - Walters, Virginia; Schindler, S. D. (New York : Viking, 1999)
A young boy describes the trip he and his father make to Grandma's house, measuring how many miles are left at various points on the trip.
Colored map on folded page preceding t.p.
Keywords: Automobile travel -- Fiction; Fathers and sons -- Fiction; Maps -- Fiction; Stories in rhyme